Cerebral glucose metabolism in idiopathic REM sleep behavior disorder is different from tau-related and α-synuclein-related neurodegenerative disorders: A brain [18F]FDG PET study. (July 2019) - Liguori, Claudio; Ruffini, Roberta; Olivola, Enrica; Chiaravalloti, Agostino; Izzi, Francesca; Stefani, Alessandro; Pierantozzi, Mariangela; Mercuri, Nicola Biagio; Modugno, Nicola; Centonze, Diego; Schillaci, Orazio; Placidi, Fabio
Abstract: Introduction: Several longitudinal studies revealed that patients affected by idiopathic REM behavior disorder (iRBD) trend to convert to α-synucleinopathies at follow-up, although the time and direction of conversion is currently unpredictable. This study aimed at evaluating brain glucose metabolism, measured by [18F]FDG-PET, in patients affected by iRBD and compared to Parkinson's Disease (PD), Lewy Body Dementia (DLB), Alzheimer's Disease (AD), and controls. Methods: Differences in brain [18F]FDG uptake were analyzed using statistical parametric mapping implemented in Matlab R2012b among iRBD, PD, DLB, AD, and controls. Results: Fifty-four iRBD, 28 PD, 10 DLB, 55 AD, and 35 controls were included in this study. iRBD patients presented an altered [18F]FDG uptake, since the increased [18F]FDG uptake in the brainstem and the reduced [18F]FDG uptake in temporal and parietal regions compared to controls. Moreover, iRBD patients showed several differences in [18F]FDG uptake than PD, DLB, or AD groups, with the main differences documented in the comparison with AD patients. Conclusions: This study documented the alteration of brain [18F]FDG uptake in brainstem and cortical areas of iRBD patients compared to controls. Moreover, the cerebral [18F]FDG uptake of iRBD patients resulted different from that presented by AD, further supporting the hypothesis that tau-related neurodegeneration may not induce RBD manifestations. However, brain [18F]FDG uptake of iRBD patients also differed from that of DLB and PD patients. Hence, these findings further support the hypothesis that iRBD may represent a very early stage of α-synucleinopathy in which biomarkers changes already occur but not allow the prediction of phenoconversion. Highlights: Brain glucose metabolism is altered in iRBD patients as expected in the early stages of neurodegeneration. iRBD patients present increased FDG uptake in the brainstem and reduced in the parietal, temporal and frontal lobes. Cerebral [18F]FDG uptake data further support the suggestion that AD neurodegeneration did not induce RBD manifestations. Brain [18F]FDG uptake in iRBD differs from LBD or PD, thus not allowing the prediction of phenoconversion.